Design and evaluation of PM Ti surfaces modified by colloidal techniques and diffusion processes for biomedical applications - Gordo, E. (2016)
The aim of this work was the modification of the composition and surface microstructure of powder metallurgy titanium to improve the wear resistance and reduce the elastic modulus while maintaining the corrosion behavior, characteristics needed for biomedical applications. For this purpose, Mo and Nb coatings were produced by colloidal techniques. Stable aqueous suspensions were prepared from micro-sized powder of Mo and Nb particles, deposited onto the powder metallurgy titanium substrates (green or sintered). After a heat treatment to promote the diffusion and the consolidation of the layers, microstructural changes were obtained. In the case of green substrates, the co-sintering process provides a diffusion depth of 85-100 micron. In the as-sintered case, a uniform depth of 40-65 microns was reached. The surfaces were characterised by micro-hardness, corrosion and tribocorrosion testing, and the results showed that hardened surfaces presented lower tendency to corrosion both under static conditions and under sliding.